PENYULUHAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL DAN MENENGAH (SAK EMKM) PADA DAHLIA BATIK GENTURAN CIANJUR - Fathonah, Andina Nur; Andriana, Nadila; Hadi, Dudi Abdul; Maryanti, Lilis; Hidayat, Rachmat (Jurnal Abdimas Bina Bangsa, 2025)
This community service activity aims to provide knowledge about Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) at Dahlia Batik Genturan Cianjur. Many batik entrepreneurs have not understood and made financial reports based on SAK EMKM. This counseling is the beginning of our activities in PkM activities and assistance will be carried out for the next stage so that MSME actors are expected to be able to make good financial reports based on SAK EMKM.